Diversity of Arbuscular Mycorrhizae Fungi in the Core Zone and Rehabilitation Zone of Gunung Halimun Salak National Park: Keragaman Fungi Mikoriza di Taman Nasional - Budi, Sri Wilarso; Arifandi, Candra Pradana; Winata, Bayu (Journal of Tropical Silviculture, 2024)
Mycorrhiza is a form of symbiosis between fungi and plant roots that can increase the absorption of plant nutrients, especially phosphorus (P). Mycorrhizal diversity is influenced by environmental conditions and the type of host plant. This study aims to assess mycorrhizal diversity in Gunung Halimun Salak National Park, particularly in the core zone (ZI) and rehabilitation zone which comprises of two ecosystems type, rehabilitation zone with reforestation (ZRR) and rehabilitation zone with agroforestry (ZRA). A total of 75 soil and root samples were taken from each location then used to observe spore diversity, spore density and arbuscular mycorrhizal fungi (AMF) colonization. The results showed that there were 8 genera of AMF found in the three locations, namely Acaulospora, Entrophospora, Dentiscutata, Diversispora, Gigaspora, Glomus, Sclerocystis and Scutellospora. The highest spore density was found in the ZI at 22.66 spores/g of soil. The Glomus and Acaulospora were the highest genera in terms of relative frequency in all sites study (100%). Glomus had the highest relative abundance in all three sites including the ZI 52.38%, ZRR 54.16% and ZRA 47.8%. AMF colonization was negatively correlated with potential P content, but positively correlated with light intensity. The highest level of colonization was found in ZRA at 59.07%. Keywords: amf, arbuscular mycorrhizal fungi, colonisation, diversity, gunung halimun salak national park, spores